Identifikasi Faktor Penghambat Kesesuaian Lahan Tanaman Bawang Merah (Allium cepa L.) di Kecamatan Parigi Kabupaten Muna - Mpia, La; Afa, Musadia; Sudarmin, Sudarmin (Jurnal Pertanian Terpadu, 2020)
This study aims to determine the factors that inhibit the growth of shallot. This research was conducted in Pargi District, Muna Regency. This study uses a free survey method with the approach of the Land Use Unit (SPL). Data processing was carried out using the method of comparison (matching) between the characteristics of the land in each SPL with the criteria of the land suitability class. The results showed that the shallot inhibiting factors in the research location include for SPL 1,2,3,5 are temperature, water availability, and rooting media; for SPL 2 are temperature, water availability, slope and erosion hazard; for SPL 7,8 are water availability and nutrient retention; and for SPL 6 are temperature and water availability.